Jews against Zionism : the American Council for Judaism, 1942-1948 - Kolsky, Thomas A. (Temple University Press, 1990)
This is the first full-scale history of the only organized American Jewish opposition to Zionism during the 1940s. Despite extensive literature on the Zionist movement, the Jewish opposition to Zionism has received only marginal and usually negative attention. In this impartial study, Thomas A. Kolsky examines the neglected phenomenon of Jewish anti-Zionism, its roots, and its results. In 1942, a number of dissident Reform rabbis founded the American Council for Judaism, the first and only Jewish organization created to fight against Zionism and the establishment of a Jewish stat.